Assessing strength and power in resistance training - Ayllon, F. N.; Jimenez, A.; Alvar, B. A.; Peterson, M. D. (Journal of Human Sport & Exercise, 2009)
Maximal Dynamic Strength is usually assessed either by the one repetition maximum test (1-RM) or by a repetition maximum test with submaximal loads, which requires the application of a formula to estimate the value of 1-RM. This value is needed to establish the objective of resistance training: such as maximum strength, endurance strength, and/or explosive strength. However, both 1-RM and submaximal tests are unable to highlight the changes produced on power and velocity. This manuscript summarizes and reviews several common strength testing protocols and proposes a novel approach that may offer greater insight to hierarchical muscle functionality